The Ecological Perspective of Landslides at Soils with High Clay Content in the Middle Bogowonto Watershed, Central Java, Indonesia - Junun Sartohadi; Nur Ainun Harlin Jennie Pulungan; Makruf Nurudin; Wahyudi Wahyudi (Applied and Environmental Soil Science, 2018)
The clay layers at hilly regions in the study area were very thick. The presence of very thick clay caused several difficulties in terms of environmental management, particularly in reducing georisk due to landslide. However, initial observations proved that areas of active landslides had better vegetation cover. The objective of this study was to find out ecological roles of landslides in livelihood in the Middle Bogowonto Watershed. The ecological roles of landslide were examined through field empirical evidences. Texture, bulk density, permeability, structure, and index plasticity were conducted for analyses of soil physical properties. Stepwise interpretation was made using 1 : 100,000–1 : 25,000 Indonesian topographic maps and remote sensing images of 30 m–<10 m spatial resolution. The results showed that landslides formed three landform zones: residual, erosional, and depositional zones. The area that did not slid, the residual zone, had massive soil structure and very hard consistency. Crops cultivated in this zone did not grow well. In the areas of active landslide, the environmental conditions seemed to be more favorable for living creatures. The landslides resulted in depositional zones with gentle slopes (4° to 15°), higher water availability, and easier soil management. The landslides also acted as the rearrangement process of landforms for better living environment.